Teacher Pedagogical Competence in the Framework of Academic Supervision Implementation at State Senior High School 1 Gubug - Ari Suci Pratiwi; Widya Kusumaningsih; Qristin Violinda (Dinasti Publisher, 2025)
Pedagogical competence is a major factor in improving the quality of education, because it includes the ability to manage learning, understand students, and develop curriculum. One of the factors that contributes to improving teacher pedagogical competence is academic supervision. This study aims to 1) describe and analyze the application of academic supervision in improving teacher pedagogical competence at SMA Negeri 1 Gubug and 2) describe and analyze the implications of the application of academic supervision in improving teacher pedagogical competence at SMA Negeri 1 Gubug. Academic supervision is carried out through three stages, namely planning, implementation, and evaluation and follow-up. The approach used in this study is qualitative descriptive research. Data were collected through observation, interviews, and documentation involving the principal, teachers, and students as research subjects. The results of the study indicate that the application of academic supervision in improving teacher pedagogical competence includes increasing teacher ability to outline learning, master learning theories and principles of educational learning, develop curriculum/syllabus, organize educational learning, utilize Information and Communication Technology, evaluate the learning process and outcomes and develop student potential. With systematic academic supervision, improving teachers' pedagogical competence can take place effectively and sustainably.